SLAVERY OF THE MAIN CHARACTER SOLOMON NORTHUP IN THE 12 YEARS A SLAVE MOVIE - Alfred Alfred; M Natsir; Ririn Setyowati (Fakultas Ilmu Budaya Universitas Mulawarman, 2017)
ABSTRACT This research revolve around a movie based on real life experience that show us about the two sides of ideology that clash between each other and the result because of it, learning from history is crucial in order to prevent society to commit the same mistake or experience the same tragedy. Descriptive qualitative approach was used in this research. The research focused on two purposes namely to identify the form of slavery that occur in the movie and the effects of slavery toward the main character Solomon Northup`s mental state during his 12 years enslavement. There are five types of slavery that occurred in the movie which are debt bondage, contract slavery, forced labor, human trafficking, and sexual slavery. Solomon showed six kinds of psychological arousal throughout the entire movie which are anger, disappointment, frustration, hate, sad, and happiness and all those emotions were related to his 12 years of enslavement. Furthermore, cognitive label was used to classify those six psychological arousals into three forms. Those three forms of cognitive label are crying, laughing, and screaming. The psychological arousal happiness belonged to both crying and laughing cognitive label. Psychological arousal anger and disappointment belong to cognitive label screaming. Psychological arousal sad and frustration belong to cognitive label crying. Key words: slavery, human rights ABSTRAK Penelitian ini mengkaji sebuah film yang diangkat dari kisah nyata. Tujuan dari penelitian ini adalah agar masyarakat bisa mengenali sejarah dan tidak mengulangi kesalahan yang sama. Pendekatan yang digunakan pada penelitian ini adalah deskriptif. Penelitian ini memiliki dua tujuan yakni mengidentifikasi bentuk-bentuk perbudakan yang terjadi dalam film dan efek perbudakan terhadap karakter Solomon Northup selama 12 tahun perbudakan yang dialaminya. Ada lima jenis perbudakan yang ditunjukkan di film, yakni perbudakan piutang, perbudakan kontrak, kerja paksa, perdagangan manusia, dan perbudakan seksual. Solomon menunjukkan enam macam dorongan psikologi, yakni amarah, kekecewaan, frustasi, benci, sedih dan bahagia, seluruh emosi itu berkaitan dengan perbudakannya selama 12 tahun. Selanjutnya, label kognitif digunakan untung mengklasifikasi keenam dorongan psikologis tersebut menjadi tiga kategori. Ketiga kategori label kognitif tersebut adalah menangis, tertawa, dan berteriak. Dorongan psikologi bahagia masuk di label kognitif menangis dan tertawa. Dorongan psikologis amarah dan kekecewaan masuk di label kognitif berteriak. Dorongan psikologi sedih dan frustasi masuk di label kognitif menangis. Kata kunci: perbudakan, hak asasi manusia